2018
DOI: 10.1038/s41598-018-35012-3
|View full text |Cite
|
Sign up to set email alerts
|

Iron homeostasis in Mycobacterium tuberculosis is essential for persistence

Abstract: Tuberculosis, caused by the obligate intracellular pathogen Mycobacterium tuberculosis (Mtb), is responsible for 2–3 million deaths annually worldwide. Intracellular adaptability, which is critical for long-term persistence, requires the pathogen to neutralize host-mediated insults. The iron–sulphur (Fe–S) cofactor is essential for many enzymes critical for such ‘adaptation’. The Mtb genome harbors only one putative iron–sulphur cluster (ISC) operon (rv1460-66) predicted to be involved in the generation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
0
28
2
Order By: Relevance
“…Two additional genes that encode the iron-dependent repressor (IdeR) and the subunit B of the SUF system (SufB) for Fe–S cluster biosynthesis also showed evidence of potential positive selection. Mutations in these genes may augment the ability of the bacilli to maintain iron homeostasis in the iron-limited environment encountered during infection 58 , 61 (Supplementary Fig. 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional genes that encode the iron-dependent repressor (IdeR) and the subunit B of the SUF system (SufB) for Fe–S cluster biosynthesis also showed evidence of potential positive selection. Mutations in these genes may augment the ability of the bacilli to maintain iron homeostasis in the iron-limited environment encountered during infection 58 , 61 (Supplementary Fig. 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In principle, switching from ISC to SUF is not the only mechanism for sustaining Fe-S assembly under ROS stress. For example, Mycobacterium tuberculosis possesses only the ISC operon, yet this pathogen is able to grow under oxidative stress including inside macrophages, presumably by up-regulating its ISC operon (32). A possible explanation is that M. tuberculosis's ISC scaffold proteins are less sensitive to ROS than those in E. coli or are repaired.…”
Section: Computing and Explaining The Environment Dependency Of Rosmentioning
confidence: 99%
“…These observations prompted us to investigate the NO-dependent phenotype of Mtb Δ sufR in vivo . Previous studies have reported the requirement of SufR for persistence of Mtb in mice [22, 53]. However, it remains to be addressed if SufR coordinates pathogen’s persistence in response to NO.…”
Section: Resultsmentioning
confidence: 99%